Manejo Reproductivo de Equinos en un Criadero de la Sabana de Bogotá (2023)
The following report describes the activities carried out in the internship that began on August 12, 2022 and ended on December 1 of the same year, at the La Marqueza hatchery, located in Tenjo, Cundinamarca. Multiple functions are performed at this site, such as: general clinical examination, reproductive checkups, calculation and administration of medications, taking and sending samples, animal welfare practices were promoted to guarantee animals optimal living conditions. In addition, veterinary practices are carried out on farms adjacent to the hatchery, in which the same functions that were carried out in the previously named hatchery were carried out.